Structural, Morphological, and Magnetic Characterization of Iron Oxide Nanoparticles Synthesized at Different Reaction Times via Thermal Decomposition Method - Dogan, Nurcan; Ozel, Fatmahan; Koten, Hasan (Bentham Science Publ Ltd, 2023)
Background Superparamagnetic Iron Oxide Nanoparticles (SPIONs) were synthesized by the thermal decomposition method. Methods In this work, the properties of the nanoparticles synthesized at different reaction times were investigated. Fourier Transformed Infrared Spectroscopy (FTIR) and thermal analysis were carried out to characterize oleate adsorbed on the surface of nanoparticles. Results The oleate-coated surfaces were obtained for all samples, and the amount of oleate on the surfaces of the particles changed with the change in reaction time. The size, size distribution, and shape of SPIONs were determined by X-ray Diffraction (XRD), transmission electron microscopy (SEM), and Dynamic Light Scattering (DLS). It was seen that changing the reaction time affected the shape of the nanoparticles, but almost the same sized nanoparticles were obtained with the increase of reaction time. The sample's crystallite size of 12.5-14.2 nm achieved with XRD is in good agreement with the mean size of 15-16.4 that was obtained by TEM results. Maximum magnetic saturation of the sample was achieved at 3 h reaction time. Conclusion The magnetic properties of iron oxide nanoparticles were characterized by Electron-Spin Resonance (ESR) and Physical Properties Measurement System (PPMS). All samples showed superparamagnetic behaviors at room temperature.
Keywords: Iron oxide nanoparticles; thermal decomposition; superparamagnetism; simulation; microemulsions; high boiling point